THE POLITICS AND POSSIBILITIES OF VICTIM‑MAKINGININTERNATIONAL LAW - Sandvik, Kristin (Revista da Faculdade de Direito do Sul de Minas, 2011)
The need to deal with the human consequences of conflict and violence remains a key challenge in global governance. As a result human experiences of suffering have become core concerns for international law in the aftermath of the Second World War. Imageries of human suffering have also become central to the idea of universalized justice which finds its particular expression in the areas of human rights, humanitarianism and international criminal law. Since the early 1990s, a proliferating number of international and national tribunals, commissions and administrative entities have been created to deal with the need for legal protection for displaced individuals, transitional justice, and restoration and allocation of criminal responsibility in the aftermath of internal and international conflict. Through a conceptual inquiry of how victim statuses are produced and allocated in international law, this paper aims to contribute to a richer socio‑legal understanding of the role of law in victim‑making in global governance.